Pier Candido Decembrio Volgarizzamento del Corpus Caesarianum. Edizione critica - Ponzù Donato, Paolo (Premio Ricerca «Città di Firenze», 2017)
The oldest translation in a modern language (vulgarization) of Caesar's commentaries, published in 1438 by Pier Candido Decembrio and dedicated to Filippo Maria Visconti and Inigo d'Avalos, is published for the first time in a critical edition. The text is presented by a rich introduction, which provides a detailed overview of the work, with particular regard to the dedications that accompany it, the style of translation and the Latin exemplar used by the humanist, recognized in a code of the Sächsische Landesbibliothek in Dresden, which, already severely damaged during World War II, was restored at the request of the author of the research at the Government of Saxony, revealing the exceptional ecdotic revision made by the Decembrium on the corpus Caesarianum. The online edition of the volume is accompanied by a special appendix to the philological introduction, which includes all the errors and lessons of the manuscripts that have passed on the vulgarization.